Approximate sub-optimum techniques for optimal power flow - Özdemır, AYDOG¯AN (Informa UK Limited, 1993)
ABSTRACT Guided by the close dependence of the real power on the bus voltage phase angles (P-8), and of the reactive power on the bus voltage magnitudes (Q-V), a new approximate formulation of power flow optimization is developed. The proposed formulation exploits this decoupling and consequently reduces the problem size, computer memory and the solution time. The method has considerable potential for real time applications. Approximate models are preferred for sub-optimization modules. The errors induced by ignored set of power flow equations, which are the major limitations common to all approximate models, are overcome by the proposed formulations.